Lightweight and static verification of UML executable models. (November 2016) - Planas, Elena; Cabot, Jordi; Gómez, Cristina
Abstract: Executable models play a key role in many software development methods by facilitating the (semi)automatic implementation/execution of the software system under development. This is possible because executable models promote a complete and fine-grained specification of the system behaviour. In this context, where models are the basis of the whole development process, the quality of the models has a high impact on the final quality of software systems derived from them. Therefore, the existence of methods to verify the correctness of executable models is crucial. Otherwise, the quality of the executable models (and in turn the quality of the final system generated from them) will be compromised. In this paper a lightweight and static verification method to assess the correctness of executable models is proposed. This method allows us to check whether the operations defined as part of the behavioural model are able to be executed without breaking the integrity of the structural model and returns a meaningful feedback that helps repairing the detected inconsistencies. Abstract : Highlights: Checking the quality of a model guarantees the quality of the final software system. Lightweight and static verifier to check the correctness of executable models. We focus on executability property of operations. Our method returns valuable feedback.